2021
DOI: 10.1021/acs.organomet.1c00014
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Aromaticity in Metallasilapentalynes

Abstract: Cyclic molecules with 4n + 2 or 4n electrons are aromatic in the lowest singlet state (S0) or the lowest triplet state (T1) according to Hückel and Baird’s rules. Thus, the design of aromatic species in both the S0 and T1 states (termed as adaptive aromaticity) is particularly challenging. In this work, we demonstrate that metallasilapentalynes show adaptive aromaticity supported by structural, magnetic, and electronic indices, in sharp contrast to metallapentalynes, which exhibit aromaticity in the S0 state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…6 and 7 depict their NICS(0) and NICS(1) zz grids, which two methods were heavily used to probe the in-plane s and out-of-plane p aromaticity of adaptive aromatics, respectively. 10,14,16,17,19,20,34 Similar results were also obtained at the B3LYP/def2-TZVP level of theory, [87][88][89] which was very recently used to study adaptive aromaticity (Fig. S7 and S8, ESI †).…”
Section: Pccp Papersupporting
confidence: 69%
“…6 and 7 depict their NICS(0) and NICS(1) zz grids, which two methods were heavily used to probe the in-plane s and out-of-plane p aromaticity of adaptive aromatics, respectively. 10,14,16,17,19,20,34 Similar results were also obtained at the B3LYP/def2-TZVP level of theory, [87][88][89] which was very recently used to study adaptive aromaticity (Fig. S7 and S8, ESI †).…”
Section: Pccp Papersupporting
confidence: 69%
“…Similarly, our previous calculations indicated that nitrosobenzene would be aromatic in both singlet and triplet states [44]. This is reminiscent of adaptive aromaticity [31][32][33], which here, was enabled by the introduction of a substituent.…”
supporting
confidence: 66%
“…A few review articles summarize these lines of evidence for the rule and explain earlier reports on various photochemical reactions on the basis of concepts related to excited-state aromaticity and antiaromaticity [29,30]. It is important to mention a recently developed concept of adaptive aromaticity by Zhu et al, referring to the small number of cyclically delocalized compounds, which show aromaticity in both singlet and triplet states [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…1c), leading to the retention of π aromaticity in the T 1 state. After that, adaptive aromaticity has also been found using theoretical calculations in osmapyridinium with phosphonium substituents, 68 metallapentalenes, and metallasilapentalynes with strong electron-donor ligands, 69,70 cyclo [10]carbon, 71 tetraatomic boron species, 72 pyrrole ring of the polycyclic dipyrrolonaphthyridinedione skeleton, 73 and the unsaturated three-membered rings. 74 In particular, the dipyrrolonaphthyridinedione has been reported by experimentalists and theoreticians as an excellent singlet fission chromophore.…”
Section: Introductionmentioning
confidence: 99%